Gene editing tools for mycoplasmas: references and future directions for efficient genome manipulation - Zhao, Gang; Lu, Doukun; Li, Min; Wang, Yujiong (Frontiers in Microbiology, 2023)
Mycoplasmas are successful pathogens that cause debilitating diseases in humans and various animal hosts. Despite the exceptionally streamlined genomes, mycoplasmas have evolved specific mechanisms to access essential nutrients from host cells. The paucity of genetic tools to manipulate mycoplasma genomes has impeded studies of the virulence factors of pathogenic species and mechanisms to access nutrients. This review summarizes several strategies for editing of mycoplasma genomes, including homologous recombination, transposons, clustered regularly interspaced short palindromic repeats (CRISPR)/Cas system, and synthetic biology. In addition, the mechanisms and features of different tools are discussed to provide references and future directions for efficient manipulation of mycoplasma genomes.